Informatisation of access to public information – opportunities and threats (Discourse of Law and Administration, 2025)
This article presents selected legal regulations as regards principles of access to public information in context of the process of informatisation of public administration. The paper addresses issues of great importance for this particular legal matter, such as: forms of access to information, the impact of development of e-governance on the legal regulation of access to public information and solutions that provide for wide objective scope of access to information. The conducted research allowed for the diagnosis of the most important opportunities and threats existing in the space of access to information and constituted an incentive to accept de lege ferenda conclusions.
Keywords: public information; access; informatisation